Outdoor Education in the Perception of Polish Preschool Teachers: A Focus Group Study - Martyna Szczotka; Katarzyna Szewczuk (Ignatianum University Press, 2023)
Objectives of the research: The aim of this study was to gather information about preschool teachers' expectations and attitudes toward outdoor education in the context of shaping and improving the quality of education. The study sought to collect material that would address the following research questions: What does outdoor education mean to preschool teachers? How do preschool teachers implement outdoor activities? What are the challenges of outdoor education according to the surveyed teachers? Research methods: The main research method used was a focus interview.  A brief description of the context of the issue: Human beings are connected to nature, we are part of it, and we live and function thanks to it. From early childhood, the natural environment is the closest and most natural for humans, and thanks to our cognitive needs and childlike perceptiveness, we immerse ourselves in the world of nature spontaneously and with great interest. Preschool teachers should see meeting children's need for curiosity and discovery of new knowledge as a challenge, and prioritize activities in this area. Furthermore, the natural environment, due to its resources, can be perceived as a workshop that teaches knowledge about the world, allows for developing children's vocabulary and shaping new concepts. It also teaches humility, patience and understanding. The environment naturally enhances the activity of children who feel comfortable in nature. Research findings: The importance of outdoor education in children's development has been discussed for years. Unfortunately, as the results of the survey suggest, this does not convince teachers to move part of the educational process outdoors. Teachers list certain limitations and shortcomings as factors that prevent the implementation of this approach in Polish preschool institutions. Conclusions and recommendations: The teachers participating in the focus groups recognize that the implementation of outdoor education activities in kindergartens is necessary, if not indispensable. They see outdoor education primarily as an opportunity for experience-based learning and connecting with nature. The teachers are sufficiently motivated to offer outdoor activities so that children can play and learn simultaneously. However, many see significant obstacles in the education system when planning outdoor learning experiences for their students. To make outdoor education more sustainable and integrated into preschool practices, it would be necessary to remove these barriers and provide support at all levels of the education system and society.